2020
DOI: 10.33448/rsd-v9i12.6111
|View full text |Cite
|
Sign up to set email alerts
|

Resgate do conhecimento etnozooterápico da Comunidade Barra do Una (Peruíbe-SP)

Abstract: Os animais são um dos recursos mais importantes para a humanidade desde os tempos primitivos. O uso destes como itens medicinais pode ser chamado de etnozoologia, sendo essa uma atividade histórica e geograficamente difundida no mundo todo. Esta pesquisa teve como objetivo resgatar e descrever o conhecimento etnozooterápico da comunidade Barra do Una, uma comunidade tradicional da Cidade de Peruíbe-SP. Foram feitas pesquisas de campo com os moradores, e os dados foram coletados por meio de questões semiestrutu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
2
0
1
Order By: Relevance
“…Didelphis spp (Linnaeus, 1758) (possum), Mesoclemmys tuberculata(Lüderwaldt, 1926) (tortoise), Cyanocorax cyanopogon (Wied, 1821) (song ) and Tamandua tetradactyla (Linnaeus, 1758) (small anteater) have been widely described. The work done byCosta- Neto (1999) andSantos and Lima (2017) also recorded the use of meat for the production of medicines among indigenous communities present in the semi-arid region of Pernambuco.Cooking Didelphis spp meat without salt or any other seasoning is recommended for the treatment of rheumatism, corroborating other works byCosta-Neto (1999) andPrado and Ramires (2020).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Didelphis spp (Linnaeus, 1758) (possum), Mesoclemmys tuberculata(Lüderwaldt, 1926) (tortoise), Cyanocorax cyanopogon (Wied, 1821) (song ) and Tamandua tetradactyla (Linnaeus, 1758) (small anteater) have been widely described. The work done byCosta- Neto (1999) andSantos and Lima (2017) also recorded the use of meat for the production of medicines among indigenous communities present in the semi-arid region of Pernambuco.Cooking Didelphis spp meat without salt or any other seasoning is recommended for the treatment of rheumatism, corroborating other works byCosta-Neto (1999) andPrado and Ramires (2020).…”
supporting
confidence: 83%
“…Among the interviewees, the use of lard, eggs, gizzards, breast gall and even chicken are used as a resource to aid in the treatment of certain diseases. Pointed out by Prado and Ramires, (2020) in their study, lard is discussed as a resource often used in the treatment of diseases that affect the respiratory system, such as sore throat, cough, phlegm in the chest, bronchitis. Finally, the healing properties presented by chicken and its by-products go further, being used to aid in the recovery process from falls, weakness, skin injuries and stomach problems.…”
Section: Resultsmentioning
confidence: 99%
“…Embora não tenha sido realizado com quilombolas, demonstra que as práticas tradicionais são transversais à construção da sociedade brasileira, constituindo-se como importante elemento da cultura nacional. 32 Apesar de a gordura de jacuraru ter notória relevância para a população que a utiliza, as indicações terapêuticas não têm comprovação científica, uma vez que já foram realizados testes para verificar a composição da gordura desse animal. 33 Neste estudo, o uso de práticas populares combinadas com quimioterápicos foi identificado como recurso nos cuidados, compatível com outra pesquisa, cujos achados revelaram combinação de recursos de cuidados da medicina formal e informal nos agravos de saúde.…”
Section: Discussionunclassified
“…Although it was not carried out with Quilombolas, it demonstrates that traditional practices are transversal to the construction of Brazilian society, constituting an important element of national culture. 32 Although jacuraru fat has a notorious relevance for the population that uses it, the therapeutic indications are not scientifically proven, since tests have already been carried out to verify the composition of the fat of this animal. 33 In this study, the use of popular practices combined with chemotherapy was identified as a resource in care, consistent with another research, whose findings revealed a combination of formal and informal medicine care resources in health problems.…”
Section: Discussionmentioning
confidence: 99%